Research on Prediction Model for Drilling Construction Progress under Uncertain Conditions - Zhai, Xitong (Scientific Journal of Technology, 2025)
Drilling engineering is a complex and high-risk operation, and its construction progress is affected by various uncertain factors, such as the complexity of geological conditions, the variability of the working environment, and the complexity of construction methods and design parameters. In order to improve the accuracy of predicting the construction progress of drilling operations, this paper studies the drilling construction progress prediction model under uncertain conditions. By analyzing the influencing factors of drilling construction progress, including geological conditions, equipment performance, and personnel operation, the drilling construction progress prediction model is studied. Two models in the paper predict the drilling construction progress by simulating random events during the drilling process under different geological conditions. The results show that the HDBN model can better predict the drilling construction progress and provides strong support for the management and decision-making of drilling engineering.